2007
DOI: 10.1038/sj.ejcn.1602929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin supplementation on breast milk concentrations of retinol, carotenoids and tocopherols in HIV-infected Tanzanian women

Abstract: Background/Objective: The effect of daily prenatal and postnatal vitamin supplementation on concentrations of breast milk nutrients is not well characterized in HIV-infected women. We examined the impact of vitamin supplementation during pregnancy and lactation on breast milk concentrations of retinol, carotenoids and tocopherols during the first year postpartum among 626 HIV-infected Tanzanian women. Subjects/Methods: We conducted a randomized, double-blind, placebo-controlled trial. Women were assigned to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Another report from this trial demonstrated that neither the multivitamins nor vitamin A affected risk of vertical transmission of HIV-1 in utero, during the intrapartum period or during the early breastfeeding periods [158]. However, this study demonstrated that vitamin A supplementation increased the risk of MTCT, pre-and perinatally [159] and through breastfeeding [131,160], if the supplementation was carried out throughout the breastfeeding period (RR = 1.38; 95% CI: 1.09-1.76; p = 0.009). Conversely, supplementation with the B vitamins and vitamins C and E reduced transmission through breastfeeding (RR: 0.37; 95% CI: 0.16-0.85; p = 0.02) in women with advanced HIV disease at baseline compared with those with high CD4 + T-cell counts [131].…”
Section: Micronutrients and Hiv Infection | Review Membrane Integrity Acontrasting
confidence: 54%
“…Another report from this trial demonstrated that neither the multivitamins nor vitamin A affected risk of vertical transmission of HIV-1 in utero, during the intrapartum period or during the early breastfeeding periods [158]. However, this study demonstrated that vitamin A supplementation increased the risk of MTCT, pre-and perinatally [159] and through breastfeeding [131,160], if the supplementation was carried out throughout the breastfeeding period (RR = 1.38; 95% CI: 1.09-1.76; p = 0.009). Conversely, supplementation with the B vitamins and vitamins C and E reduced transmission through breastfeeding (RR: 0.37; 95% CI: 0.16-0.85; p = 0.02) in women with advanced HIV disease at baseline compared with those with high CD4 + T-cell counts [131].…”
Section: Micronutrients and Hiv Infection | Review Membrane Integrity Acontrasting
confidence: 54%
“…70 The three supplementation arms, including those with vitamin A, decreased the burden of malaria in this cohort. 61 Other reports from this trial, however, also described adverse effects, such as increased vertical transmission and increased viral load in breast milk with vitamin A supplementation, without reduction in mortality, 81,[83][84][85] and risk of developing subclinical mastitis with multivitamins. 84 In contrast, Kumwenda et al 98 randomized a cohort of 697 pregnant women in Malawi to receive 3 mg daily of retinol or placebo, in addition to the standard iron and folate supplementation during pregnancy, and concluded that supplementation during pregnancy and postpartum had beneficial effects on newborns' birth weight and prevention of anemia, without changing the rate of mother-to-child transmission.…”
Section: Rcts Of Micronutrients In Art-naïve Plwhmentioning
confidence: 99%
“…81 Multivitamins alone or with vitamin A improved maternal weight gain during the third trimester of pregnancy. 80 Multivitamins during pregnancy and breastfeeding reduced adverse pregnancy and child outcomes, 72 including improving newborns' ponderal weight 71 and vitamin E status, 83 protecting infants against motor developmental delays, 64 reducing maternal wasting, 65 hypertension, 69 symptoms of depression, improving women's quality of life, 63 delaying HIV disease progression during pregnancy, 25 and improving hematological outcomes in both mothers and infants. Supplementation with vitamin A during pregnancy improved the vitamin A status of infants.…”
Section: Rcts Of Micronutrients In Art-naïve Plwhmentioning
confidence: 99%
“…Because vitamin A and b-carotene were administered together in this trial, it is not possible to ascertain the individual effect of each nutrient following an intent-to-treat analytic approach. Nevertheless, in an effort to identify the separate effects of each nutrient, we evaluated the associations between viral or proviral HIV concentrations and retinol or b-carotene concentrations in breast milk using an observational, cross-sectional design in which we took advantage of the treatment's large effect on the variability of breastmilk nutrient concentrations (11). A key aspect of these analyses was the simultaneous adjustment for retinol and b-carotene concentrations in the models to overcome confounding of the effect of one nutrient by the other's given that they shared the same major source (treatment assignment) in half of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Retinol and b-carotene concentrations were quantified in the whole-milk aliquot with the use of HPLC (Restek Corp, Bellefonte, PA), as previously described in detail (11). The minimum detection limits were 3.12 and 1.65 nmol/L for retinol and b-carotene, respectively.…”
Section: Laboratory Methodsmentioning
confidence: 99%